Soviets in International Organizations : Changing Policy toward Developing Countries, 1953-1963 - Rubinstein, Alvin Z. (Book collections on Project MUSE., 1964)
Focusing on the relationship between the Soviet Union and the leading Afro-Asian neutralists, Professor Rubinstein studies Soviet policy and behavior in international organizations concerned with promoting the economic and social welfare of developing countries. He has made a thorough examination of the records of many such organizations, including the Economic and Social Council, the Technical Assistance Committee, and the International Labor Organization. To gain insight into the conduct and objectives of Soviet representatives at meetings of these groups, and into the behavior of Soviet nationals employed in international secretariats, the author undertook extensive interviewing of neutralist, Communist, and Western officials in New York, Geneva, Vienna, Bangkok, and New Delhi.Originally published in 1964.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.